2019
DOI: 10.1038/s41598-018-38227-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between decreased serum TBIL concentration and immediate memory impairment in schizophrenia patients

Abstract: Cognitive impairment is a core feature of schizophrenia (SCH). In addition to the toxic effect of Bilirubin (BIL), it has antioxidant properties that were associated with the psychopathology and cognitive impairment of psychiatric disorders. The aim of this study was to examine the correlation of serum total BIL (TBIL) concentration with cognitive impairment in SCH patients. We recruited 34 SCH patients and 119 healthy controls (HCs) in this case-control design. Cognition was assessed using the Repeatable Batt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 50 publications
5
13
2
Order By: Relevance
“…However, the correlation between bilirubin and WMSIII-LNS were only significant at 10 percent level (see Supplementary Table S5 online). We are hereby able to confirm the findings seen in chronic patients with schizophrenia in the study by Yin et al 24 , but here in individuals with FEP, at the same time addressing the influence of antipsychotic medication, BMI, smoking and alcohol, as requested by the authors 24 .…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…However, the correlation between bilirubin and WMSIII-LNS were only significant at 10 percent level (see Supplementary Table S5 online). We are hereby able to confirm the findings seen in chronic patients with schizophrenia in the study by Yin et al 24 , but here in individuals with FEP, at the same time addressing the influence of antipsychotic medication, BMI, smoking and alcohol, as requested by the authors 24 .…”
Section: Discussionsupporting
confidence: 84%
“…Equivalent to our findings, Yin et al found reduced levels of bilirubin in two weeks antipsychotic-free patients with chronic schizophrenia compared with HC 24 . In line with our study, bilirubin was positively correlated with memory, although immediate memory, in individuals with schizophrenia but not in HC.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations